2012
DOI: 10.1186/1471-2164-13-202
|View full text |Cite
|
Sign up to set email alerts
|

Comparing thousands of circular genomes using the CGView Comparison Tool

Abstract: BackgroundContinued sequencing efforts coupled with advances in sequencing technology will lead to the completion of a vast number of small genomes. Whole-genome comparisons represent an important part of the analysis of any new genome sequence, as they can provide a better understanding of the biology and evolution of the source organism. Visualization of the results is important, as it allows information from a variety of sources to be integrated and interpreted. However, existing graphical comparison tools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
206
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(207 citation statements)
references
References 10 publications
1
206
0
Order By: Relevance
“…The genomic organization and annotation of the seven previously reported ViI-like enterobacterial bacteriophages (26) were used to determine the location of ORF1 in MAM1. The CGView comparison tool (27) was employed to visualize the MAM1 genome and to generate Fig. 3.…”
Section: Methodsmentioning
confidence: 99%
“…The genomic organization and annotation of the seven previously reported ViI-like enterobacterial bacteriophages (26) were used to determine the location of ORF1 in MAM1. The CGView comparison tool (27) was employed to visualize the MAM1 genome and to generate Fig. 3.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12] were reported by the same research group [28], and contained two complicated inversions. One was nested between 3 and 7 o'clock direction and between 4 and 6 o'clock direction.…”
Section: Three Types Of Genome Rearrangements In H Pylorimentioning
confidence: 99%
“…Several visualizers have been proposed to date [10][11][12][13], but our approach is unique in that we do not presuppose binary comparison between genomes. Comparison against a single reference implicitly assumes the perfection of the reference data.…”
Section: Introductionmentioning
confidence: 99%
“…The linear mimivirus genome is depicted as a circle starting from the site indicated by an arrow. The figure was constructed with the CGView Comparison Tool (CCT) (46). tions revealed that a substantial reduction of their genome specifically occurred at the edges of the genome (35).…”
Section: Figmentioning
confidence: 99%